Puroindoline genes introduced into durum wheat reduce milling energy and change milling behavior similar to soft common wheats. (September 2016) - Heinze, K.; Kiszonas, A.M.; Murray, J.C.; Morris, C.F.; Lullien-Pellerin, V.
Abstract: Grain physical characteristics and milling behavior of a durum wheat line in which both wild-type puroindoline genes were translocated and stabilized after backcrossing ( Svevo-Pin ) were compared with the parent line (Svevo) . The only observed differences between grain characteristics were the mechanical resistance and starchy endosperm porosity revealed through vitreosity measurement. A significant increase of flour and a decrease of semolina yield and break milling energy were observed from Svevo-Pin in comparison with the non-recombinant parent line in accordance to the lower grain mechanical resistance and higher porosity measurements. Moreover, the particle size distribution shown for Svevo-Pin flour appeared consistent with a lower adhesion between starch granules and the protein matrix attributed to the presence of wild-type puroindolines. Coarse bran yield was conversely increased. This appeared to be due to a lower starchy endosperm recovery as a higher proportion of grain starch was found in this bran fraction. Flour from the durum parent line was inversely enriched in phytic acid, a cellular marker of the aleurone layer. Starch damage was also lower in Svevo-Pin flours in comparison with Svevo . All of the observed differences between translocation and parent lines were confirmed independent of the culture growth conditions (n = 12). Highlights: Wild-type puroindolines introduced in durum wheat reduces the grain grinding energy. Flour yield, particle size and tissue distribution were also modified. Starch damage reduction was observed in durum wheat grains possessing puroindolines. Differences in milling behavior were observed independent of environmental conditions.